Examining the Value of Jury Critique for Architectural Design Studio Courses - Santos, Frederick (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 7, 2020)
A common evaluation tool used in an architectural design studio course is the critique. The critique is the process by which students present their final design work as answer to a design problem, have their work examined, and receive feedback on their work from a jury while being observed by faculty and fellow students. The jury in the study were instructors and design professionals with no involvement in conducting the studio courses prior to final critique, while the faculty were instructors who officially handled said courses during the semesters. Students’ works were then given scores by both faculty in-charge and jury, with the scores weighted within the students’ final grades based on the evaluation method and criteria designed by the faculty in-charge. While a common occurrence in architecture design studio courses, the value of jury critique has not been adequately examined. It is unclear if the value of jury critique lies in student grading, evaluation approaches, or both. Under these parameters, the study aims to investigate the degree of similarities and disparities between jury and faculty as well as among jurors in evaluating final output through jury critique. This was performed using statistical analysis, where the variable observed was scores given by juries to students that presented their Design course plates, in addition to surveys of jurors who have taken part in courses covered by the study. Particularly, average jury scores were compared to faculty scores and individual juror scores were compared with each other in an attempt to find a pattern of agreement or disagreement among evaluators, with survey responses used to complement and add significance to statistical analysis. A key finding was that a value of jury critique is its ability to accurately evaluate students’ output without the potential biases that faculty may have from being reflected in the students’ grades. This is significant as a basis to guide how to appropriately use juries as evaluators of students’ plates and how grading responsibilities may be divided among jury and faculty. Recommendations were then made based on findings to maximize its effectivity within the architecture design studio course. Keywords: Jury Critique, Jury Grading, Architectural Design Studio, Architectural Design Evaluation, Architectural Design Assessment, Evaluation Approach